ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN BESAR BARANG PRODUKSI DAN SUB SEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Achmad Tjahjono; Vica Novica Chaerulisa (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
This study aims to determine differences in companies that implement the FIFO inventory accounting methods and average taking into account the size of the company, inventory intensity and variability of cost of goods sold as the independent variable. The data used were obtained from the company financial statements trade sub-sector of the goods production and retail trade sub-sectors listed on the Stock Exchange. The data used for this study is the application of the accounting methods of data measured using dummy variables, namely by giving the average value of 0 to a method and a value of 1 to the FIFO method. Other data used is the size of the company, inventory intensity, variability of cost of goods sold. The method used in this research is descriptive method. These samples included 22 companies sub-sector of the trade of the goods production and retail trade subsectors listed on the Stock Exchange during the period 2010-2013. Tests used descriptive statistics, hypothesis testing, Test F and Test Coefficient of Determination with  = 0.05. The process of statistical analysis using SPSS statistical application program 20. Based on the research that the selection method of inventory accounting effect on the size of the company, but has no effect on the intensity and variability of inventory cost of goods sold.